2022
DOI: 10.1101/2022.04.19.488819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microglial inflammatory activation paradoxically improves glucose tolerance during diet-induced obesity

Abstract: Hypothalamic gliosis associated with high fat diet (HFD) feeding increases susceptibility to hyperphagia and weight gain, and is therefore presumed to promote obesity-associated consequences such as glucose intolerance as well. Nevertheless, the body weight-independent contribution of microglial activation to glucose regulation has not been determined. Here we show that reducing microglial NF-κB signaling via cell-specific IKKβ deletion exacerbates HFD-induced glucose intolerance and insulin resistance despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…A recent study (preprint) has unexpectedly shown that microglial inflammation, induced by Gq‐DREADD activation, improved glucose tolerance, both in lean and obese mice. This effect depended on TNF‐α signaling in microglia, which increased the activity of hypothalamic glucoresponsive neurons (Douglass et al, 2022). Glucose intolerance is also observed in other diseases as diabetes mellitus (Malone & Hansen, 2019), chronic kidney disease (Spoto et al, 2016), and cystic fibrosis (Kasim et al, 2021).…”
Section: Application Of Dreadds In Microgliamentioning
confidence: 99%
“…A recent study (preprint) has unexpectedly shown that microglial inflammation, induced by Gq‐DREADD activation, improved glucose tolerance, both in lean and obese mice. This effect depended on TNF‐α signaling in microglia, which increased the activity of hypothalamic glucoresponsive neurons (Douglass et al, 2022). Glucose intolerance is also observed in other diseases as diabetes mellitus (Malone & Hansen, 2019), chronic kidney disease (Spoto et al, 2016), and cystic fibrosis (Kasim et al, 2021).…”
Section: Application Of Dreadds In Microgliamentioning
confidence: 99%